CONTROL GROUP ANALYSIS OF RENAL STRUCTURE IN 9-MONTH-OLD WHITE RATS USING MORPHOMETRIC AND HISTOLOGICAL METHODS - Kaymanova Kamila Imamovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
The kidney is a complex and highly specialized organ responsible for maintaining homeostasis through regulation of water–electrolyte balance, blood pressure, and elimination of metabolic waste. Quantitative morphometric and histological analyses provide reliable indicators of the functional and structural status of the kidney, and their changes often reflect early manifestations of pathology. Establishing baseline parameters in intact experimental animals is therefore critical for comparative nephrology, especially in studies focused on renal injury, aging, or systemic disease